APLIKASI TEKNOLOGI PENDIDIKAN BERSAMA PENDIDIK PROFESIONAL: SUATU STRATEGI INOVATIF PENINGKATAN MUTU PENDIDIKAN - Isminiati, Christina (Dinamika Pendidikan, 2015)
Educatton plays a very important role in improving the quality of Indonesia's human resources (HR) so that the quality development or the quality of education needs to be continually made by improving the quality of learning. In improving the quality of learning the role of teachers is very important and strategic,· therefore the teachers need to master the four required competencies as the professional teacher in carrying out the task of educating the pedagogic competence, professional, personality, and social competence. Professional educators not only deliver learning materials that exist in the text book, but also to design and the. u~e of educational technology in learning.